Influence of music therapy on the well-being and mental health of university students: a systematic literature review - Bravo-Fuentes, Paloma (Revista de Investigación en Musicoterapia, 2025)
Music therapy, recognised for its benefits in mental health and emotional well-being, is explored in this systematic review as an intervention for university students facing academic and personal stress. This article evaluates how music therapy can positively contribute to academic performance and foster a healthy educational experience, considering the unique challenges faced by this population group. In addition, it examines the ability of music therapy to provide a space for emotional expression and social connection, crucial for the management of certain common emotional disorders in students. Using the PRISMA protocol, an exhaustive search was conducted to select peer-reviewed studies published since 2019, focusing on the effectiveness of music therapy in university contexts. The main conclusion highlights the importance of integrating music therapy into university support services, proposing a holistic approach to improve the mental health and general well-being of students.